2020
DOI: 10.3390/polym12030669
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Properties of GnP–PA-Extruded Films

Abstract: It is generally known that significant improvements in the properties of nanocomposites can be achieved with graphene types currently commercially available. However, so far this is only possible on a laboratory scale. Thus, the aim of this study was to transfer results from laboratory scale experiments to industrial processes. Therefore, nanocomposites based on polyamide (PA) and graphene nanoplatelets (GnP) were prepared in order to produce membranes with improved gas barrier properties, which are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A decrease in chain spacing leads to an increase in intermolecular interaction strength and a higher degree of material compaction. It can be obtained by wide-angle X-ray diffraction (WAXD) [42]. The D-spacing is inversely proportional to the diffraction angle corresponding to the prominent diffraction peak.…”
Section: D-spacing Of Hdpementioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in chain spacing leads to an increase in intermolecular interaction strength and a higher degree of material compaction. It can be obtained by wide-angle X-ray diffraction (WAXD) [42]. The D-spacing is inversely proportional to the diffraction angle corresponding to the prominent diffraction peak.…”
Section: D-spacing Of Hdpementioning
confidence: 99%
“…ray diffraction (WAXD) [42]. The D-spacing is inversely proportional to the diffr angle corresponding to the prominent diffraction peak.…”
Section: D-spacing Of Hdpementioning
confidence: 99%
“…The compaction process allowed loading up to 20 wt% of GNPs in PA6 and showed that the compaction process did not hinder dispersion of GNPs or their thermal properties. Boldt et al 84 developed PA/GNP nanocomposites at a laboratory scale and a semi-industrial level using flat film extrusion. The nanocomposites were applied to make membranes with better-quality gas barrier properties at laboratory scale.…”
Section: Melt Blendingmentioning
confidence: 99%
“…polyamide [10] and polycarbonate [11], compounded by means of extrusion, have been reported. However, in order to ensure lower cost and processability, as low as possible filler concentrations are usually recommended.…”
Section: Introductionmentioning
confidence: 99%
“…First, the composites are usually produced by the compression molding technique and it is known that the barrier properties depend significantly on the manufacturing technique [13]. Thus, those results are not directly transferable [10] to commonly used fabrication techniques in the flexible packaging industry, like blown and cast films processes. Second, the most commonly used thermoplastic in the polymer packaging industry is polyethylene [14].…”
Section: Introductionmentioning
confidence: 99%